Experimental Study on Coal and Gas Outburst Risk in Strong Outburst Coal Under Different Moisture Content - Lu, Zhuang; Wang, Liang; Lv, Mingzhe; Lei, Yang; Wang, Hao; Liu, Qingquan (Frontiers in Earth Science, 2022)
Coal and gas outburst is the extremely serious dynamic phenomenon under the comprehensive action of many factors, which is still a major disaster to be solved in coal mine production at present. Considering the significant influence of moisture content on coal and gas outburst, it is necessary to carry out experimental research on coal and gas outburst under different moisture content conditions. The coal of the serious outburst coal seam in the Luling coal mine, which has had several coal and gas outburst accidents, was selected as the experimental sample. Firstly, the gas desorption law and outburst index characteristics of coal under different moisture content were studied, and the influence of moisture content on gas outburst parameters of coal were obtained. Then the simulation tests of coal and gas outburst under different moisture content were carried out by using a triaxial coal and gas outburst simulation test system. Based on the above experimental research, the influence of moisture on coal and gas outburst was summarized, and the energy calculation and prevention countermeasures of coal and gas outburst under different moisture content conditions were carried out. With the increase of moisture content, the adsorption constant a, the initial velocity of gas diffusion Δp and the gas desorption index of drill cuttings K1/Δh2 decreases, but the Protodyakonov coefficient f increases, all of which have exponential relation with moisture content. Meanwhile, with the increase of moisture content, the threshold of coal and gas outburst pressure increases, and intensity and energy of outburst decreases. At 0.45 MPa pressure, the outburst of 1.47 % moisture content is the most serious, the outburst of 5 % moisture content is weakened, while the outburst of 10% moisture content are not triggered. 5 % moisture content can be used as a critical index of hydraulic measures to prevent coal and gas outburst in No. 8 coal seam of the Luling coal mine. The research of this paper can provide a new idea for the theoretical study of coal and gas outburst in serious outburst coal seams and the control of coal and gas outburst by hydraulic measures.